ORPHEUS AND THE VANISHING NOTE: xenosonics, katabasis, daemonotechnics. Issue 3 (4th May 2018) - Blake, Charlie
Abstract: It is by now something of a commonplace for readers of Blanchot to claim that the limpid quality of his prose and the wealth of allusion woven through even his more opaque writings often have the paradoxical effect of making his work both engagingly lucid and approachable and utterly resistant to interpretation or even comprehension in any ordinary sense. At the core of this paradoxical experience is a theory of creativity that Blanchot frequently alludes to and often appears to be about to reveal before allowing it to vanish into what he calls his "third night, " a darkness beyond both day and night, being and non-being, from which the artist, writer or composer draws the inspiration required for both the initiation and completion of the textual artefact or, as will be argued here, the musical event. Focusing on the myth of Orpheus and Eurydice that Blanchot outlines most fully in "The Gaze of Orpheus, " and deploying this writer's own theory and practice of xenosonics, the fundamental question here will be – and to borrow from his friend Bataille – the "use-value" of Blanchot's evasive theory of creativity for the creator of music, text or art.